Water rights in informal economies in the Limpopo and Volta basins - van Koppen, Barbara (CGIAR Challenge Program on Water and Food, 2010)
Most African countries underwent water legislation reform since the 1990s, through which existing plural legal systems were changed into nation-wide permit systems, in which the state acts as custodian of the nation’s water resources. Although globally heralded as the best way to manage water resources within the broader context of Integrated Water Resource Management, this project examines the problematic implications of the new laws for the majority of the rural and peri-urban poor. Since time immemorial, their water access has been largely governed by self-supply and informal arrangements that have allowed them to survive in often harsh ecological conditions. Water law reform basically dispossesses them from their current and future claims to water, unless they adopt an administrative water rights system that also historically has favored administration-proficient foreign investments. As the new laws have hardly been implemented as yet for various reasons that are further explored in this research, this research provides a timely analysis of the processes at stake and identifies alternative legal tools that recognizes informal water arrangements thereby protecting and encouraging small-scale water users to expand their water use. The generic findings from Burkina Faso, Ghana, Mozambique, and South Africa have generic validity throughout Sub-Saharan Africa.